2022
DOI: 10.3389/fmicb.2022.788893
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas stutzeri and Kushneria marisflavi Alleviate Salinity Stress-Associated Damages in Barley, Lettuce, and Sunflower

Abstract: Soil salinity is one of the most important abiotic factors limiting plant productivity. The aim of this study was to determine the effect of selected halotolerant plant growth-promoting endophytes (PGPEs, Pseudomonas stutzeri ISE12 and Kushneria marisflavi CSE9) on the growth parameters of barley (Hordeum vulgare), lettuce (Lactuca sativa), and sunflower (Helianthus annuus) cultivated under salt stress conditions. A negative effect of two higher tested salinities (150 and 300 mM NaCl) was observed on the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The effects of salinity caused by NaCl on plant physiology are common ( Fageria et al., 2012 ). The previous study also shows that increased concentrations of NaCl have an adverse effect on morphology in other plants, such as Dracocephalum moldavia L. ( Mohammadi et al., 2021 ), Ocimum basilicum L. ( Lazarević et al., 2021 ), Oenanthe javanica ( Kumar et al., 2021 ), Suaeda salsa ( Zhang et al., 2020 ), Glycine max L. ( Jabeen et al., 2021 ), Hordeum vulgare , Lactuca sativa , and Helianthus annuus ( Szymańska et al., 2022 ). High Na + interferes with the allocation of other important minerals and reduces water uptake; it alters membrane lipids and induces ROS generation, leading to lipid peroxidation, resulting in a decrease in RWC, photosynthetic pigments, and an increase in El, proline content, DPPH activity in M. longifolia.…”
Section: Discussionmentioning
confidence: 91%
“…The effects of salinity caused by NaCl on plant physiology are common ( Fageria et al., 2012 ). The previous study also shows that increased concentrations of NaCl have an adverse effect on morphology in other plants, such as Dracocephalum moldavia L. ( Mohammadi et al., 2021 ), Ocimum basilicum L. ( Lazarević et al., 2021 ), Oenanthe javanica ( Kumar et al., 2021 ), Suaeda salsa ( Zhang et al., 2020 ), Glycine max L. ( Jabeen et al., 2021 ), Hordeum vulgare , Lactuca sativa , and Helianthus annuus ( Szymańska et al., 2022 ). High Na + interferes with the allocation of other important minerals and reduces water uptake; it alters membrane lipids and induces ROS generation, leading to lipid peroxidation, resulting in a decrease in RWC, photosynthetic pigments, and an increase in El, proline content, DPPH activity in M. longifolia.…”
Section: Discussionmentioning
confidence: 91%
“…In Carreiras’s [ 34 ] research on Halimione portulacoides , both uninoculated and inoculated plants showed significant pigment changes under salt treatments. Szymańska et al [ 61 ] found that halotolerant endophytes ( Pseudomonas stutzeri ISE12 and Kushneria marisflavi CSE9) positively affected chlorophyll levels, leaf morphology, water retention, root growth and biomass accumulation in Hordeum vulgare , Lactuca sativa and Helianthus annuus under salt stress. They suggested that introducing halotolerant bacteria to crops could alleviate salt stress and enhance growth, emphasizing the importance of strain compatibility and validating universal plant stress indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis AtWSD1 was up regulated under several abiotic stresses and activate wax biosynthesis in response to environmental stresses. Sunflower growth and productivity are greatly affected by abiotic stresses such as salinity, drought and cold (Allinne et al, 2009;Fulda et al, 2011;Szymańska et al, 2022). The expression of 12 HaWSD genes under different stresses revealed that most of genes can be induced significantly by exogenous ABA and PEG-induced drought stress in sunflower stems, leaves and roots (Figure 3).…”
Section: Discussionmentioning
confidence: 99%